Remoção de calor e controle de temperatura da fermentação alcoólica extrativa empregando CO₂ - Campos, Brenda Gomes (Universidade Federal de São Carlos, 2024)
Brazil is the world’s largest producer of sugarcane ethanol. However, alcoholic fermentation still faces significant challenges, such as the inhibitory effect of ethanol and the difficulty in temperature control. Extractive fermentation with carbon dioxide (CO₂) stripping has shown promise, as it allows for the use of more concentrated sugar musts, resulting in a higher total ethanol concentration. This process also facilitates the removal of heat generated by the yeasts. In this context, the present work proposes an innovative approach by investigating temperature control through the manipulation of CO₂ volumetric flow rates in extractive fed-batch fermentations. A mathematical model of the process was developed, and simulations were performed to identify ideal flow rate values that would maintain a constant broth fermentation temperature throughout the process. The following control strategies were investigated: 1) Feedback control using an on/off controller in closed loop, adjusting the CO₂ flow rate to maintain fermentation temperature at 34 °C; 2) Optimization of CO₂ volumetric flow rates (one flow rate per subinterval), by dividing the stripping interval into different subintervals (1, 2, 4, 8, 16, and 32), in simulated fermentations at temperatures of 30, 32, and 34 °C; and 3) Optimization of CO₂ volumetric flow rates inspired by model predictive control. Experimental results confirmed the effectiveness of the proposed strategies. In the first strategy, the temperature was maintained close to the desired value (34 °C) using a constant CO₂ flow rate of 12 L/min. In the second strategy, the temperature deviation was 0.5 °C, using eight optimal CO₂ flow rates. In the third strategy, the temperature was maintained at 35 °C with a deviation of less than 1 °C, employing 84 CO₂ flow rates values. This final strategy resulted in the lowest total CO₂ amount, with a reduction of approximately 14.7% compared to the others. The approach demonstrated that the use of CO₂ is effective in removing heat generated during the process and in temperature control, overcoming one of the limitations of fermentation, especially in units located in hot climates. Additionally, this approach may reduce or even eliminate the need for water for cooling fermentation vats.
Heat Removal and Temperature Control in Extractive Alcoholic Fermentation using CO₂
Keywords: Fermentação alcoólica; Dióxido de carbono; Controle de temperatura; Modelagem matemática; Otimização da vazão de CO₂; Fermentação extrativa; Ethanol fermentation; Carbon dioxide; Temperature control; Mathematical modeling; CO₂ flow rate optimization; Extractive fermentation; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA